Genre knowledge in disciplinary communication : - Berkenkotter, Carol (L. Erlbaum Associates, 1995)
The authors' studies of disciplinary communication examine operations of systems as diverse as peer review in scientific publications and language in a first grade science classroom. The methods used include case study and ethnographic techniques, and rhetorical and discourse analysis